The effects of prolonged pacifier use on language development in infants and toddlers - Kanellopoulos, Alexandros K.; Costello, Sarah E. (Frontiers in Psychology, 2024)
Pacifiers are a common soothing tool used by parents to calm and comfort infants and toddlers. While pacifiers can provide temporary relief, there is growing concern about the potential long-term effects of prolonged pacifier use on language development. Previous studies have suggested that prolonged use of pacifiers may have negative consequences on language outcomes in children during the first few years of life. Previous studies have shown that prolonged use of pacifiers has smaller vocabulary sizes at 2 years of age. In addition, significant association between greater frequency of daytime pacifier use and worsening of cognitive outcomes was shown. Furthermore, research has shown a strong dose-response association between intense pacifier use up to 4 years of age and lower IQ at 6 years. Recently, the importance of oral motor movements and sensorimotor production for speech perception in infants as young as 6 months has been highlighted, raising important questions on the effect of oral motor movement restrictions at an early age. Together, these findings raise concern about the potential long-term effects of prolonged pacifier use on language and cognitive development at a critical time in child development. However, it is still inconclusive and debatable within the scientific field the potential relationship between pacifier use and language development in early life most likely due to the complexity of studying child development. This mini review aims to provide valuable insights for parents, caregivers, and healthcare professionals in making informed decisions and understand regarding pacifier use for children.